Bedside assessment of regional cerebral perfusion using near-infrared spectroscopy and indocyanine green in patients with atherosclerotic occlusive disease - Hiroshi Saito (Nature Portfolio, 2018)
Abstract This pilot study aimed to investigate the utility of near-infrared spectroscopy/indocyanine green (NIRS/ICG) for examining patients with occlusive cerebrovascular disease. Twenty-nine patients with chronic-stage atherosclerotic occlusive cerebrovascular disease were included. The patients were monitored using NIRS at the bedside. Using ICG time-intensity curves, the affected-to-unaffected side ratios were calculated for several parameters, including the maximum ICG concentration (ΔICGmax), time to peak (TTP), rise time (RT), and blood flow index (BFI = ΔICGmax/RT), and were compared to the affected-to-unaffected side ratios of the regional cerebral blood flow (rCBF) and regional oxygen extraction fraction (rOEF) obtained using positron emission tomography with 15O-labeled gas. The BFI ratio showed the best correlation with the rCBF ratio among these parameters (r = 0.618; P = 0.0004), and the RT ratio showed the best correlation with the rOEF ratio (r = 0.593; P = 0.0007). The patients were further divided into reduced rCBF or elevated rOEF groups, and the analysis revealed significant related differences. The present results advance the measurement of ICG kinetics using NIRS as a useful tool for the detection of severely impaired perfusion with reduced rCBF or elevated rOEF. This method may be applicable as a monitoring tool for patients with acute ischemic stroke.